1994
DOI: 10.7164/antibiotics.47.740
|View full text |Cite
|
Sign up to set email alerts
|

The squalestatins, novel inhibitors of squalene synthase produced by a species of Phoma. V. Minor metabolites.

Abstract: The isolation and structure determination by 1H and 1 3C NMRand MSof24 novel squalestatins from cultures of Phoma sp. C2932 is described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(24 citation statements)
references
References 0 publications
1
23
0
Order By: Relevance
“…Squalestatin 1 exhibits broad-spectrum antifungal activity [ 64 ] and was identified in Phoma sp. and several ascomycetes [ 65 , 66 ]. AbT1 (100% similarity) is a precursor of the cyclic peptide antibiotic Aureobasidin A (AbA), known to be produced by Aureobasidium pullulans [ 67 ].…”
Section: Resultsmentioning
confidence: 99%
“…Squalestatin 1 exhibits broad-spectrum antifungal activity [ 64 ] and was identified in Phoma sp. and several ascomycetes [ 65 , 66 ]. AbT1 (100% similarity) is a precursor of the cyclic peptide antibiotic Aureobasidin A (AbA), known to be produced by Aureobasidium pullulans [ 67 ].…”
Section: Resultsmentioning
confidence: 99%
“…C2932. These were later followed by 19 other squalestatins differing by the structure of O-acyl radicals and bicyclooctane nucleus [83].…”
Section: Antibiotics Inhibiting the Late Stages Of Cholesterol Biosynmentioning
confidence: 99%
“…The triacid 1 was the first natural product found to be a potent inhibitor of squalene synthase and it also exhibited broad-spectrum antifungal activity. Because of its extraordinary potency, the triacid 1 and structurally related congeners such as 6,7-dideoxysqualestatin H5 (DDSQ, 2) 7 represented exciting new therapeutic leads in the treatment of DDSQ (2) In the summer of 1993, with the support of a Nuffield Foundation undergraduate research bursary award, Vittorio Caprio (now at Manchester Metropolitan University) found that a glyoxylate can function as a dipolarophile with a carbonyl ylide and that it reacted with the desired regiochemistry, but undesired exo/endo stereochemistry. Nevertheless, this preliminary result assisted a research grant application to the UK Science and Engineering Research Council (SERC), which was assessed by an organic chemistry subcommittee who could recommend earmarked studentships to the chemistry committee ( Figure 2).…”
Section: Introductionmentioning
confidence: 99%